An agenda-setting paper on data sharing platforms: euCanSHare workshop [version 2; peer review: 2 approved] - Thijs Devriendt; Clemens Ammann; Folkert W. Asselbergs; Alexander Bernier; Rodrigo Costas; Matthias G. Friedrich; Josep L. Gelpi; Marjo-Riitta Jarvelin; Kari Kuulasmaa; Karim Lekadir; Michaela Th. Mayrhofer; Vaclav Papez; et al. (Open Research Europe, 2021)
Various data sharing platforms are being developed to enhance the sharing of cohort data by addressing the fragmented state of data storage and access systems. However, policy challenges in several domains remain unresolved. The euCanSHare workshop was organized to identify and discuss these challenges and to set the future research agenda. Concerns over the multiplicity and long-term sustainability of platforms, lack of resources, access of commercial parties to medical data, credit and recognition mechanisms in academia and the organization of data access committees are outlined. Within these areas, solutions need to be devised to ensure an optimal functioning of platforms.